Characterization of composites based on natural and glass fibers obtained by vacuum infusion - Rodriguez, Exequiel Santos (2005)
The mechanical properties of composites based on different natural fibers and glass fibers using unsaturated polyester and modified acrylic as matrix are evaluated. In spite of the several works done in natural fiber composites, there are very few results on acrylic as matrix. Fabrication of the composites is done by means of vacuum infusion. Flexural, tension, and impact test are conducted on the composites. Ignition, thermal degradation, and water absorption are determined. Jute composite with unsaturated polyester resin as matrix showed the best results on flexural and tensile strengths and the lowest in impact energy, because of the strong interphase developed. Flax composites show higher impact energy than the other natural fiber composites, due to the existence of the effective energy dissipation mechanisms, like pull-out and axial splitting of the fibers. Scanning electron micrograph confirmed this fact. None of the samples resisted the five-second exposition to the flame on the ignition test. All of them were completely consumed, and flax composites burned the longest.